2022
DOI: 10.1093/nc/niac013
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the veil of duality—topographic reorganization model of meditation

Abstract: Meditation can exert a profound impact on our mental life, with proficient practitioners often reporting an experience free of boundaries between a separate self and the environment, suggesting an explicit experience of “nondual awareness.” What are the neural correlates of such experiences and how do they relate to the idea of nondual awareness itself? In order to unravel the effects that meditation has on the brain’s spatial topography, we review functional magnetic resonance imaging brain findings from stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 185 publications
0
8
0
Order By: Relevance
“…The review by Cooper et al (2022) found that the results on mPFC activity was the most divergent of all network hubs investigated, which could be an indication that this area is especially prone to a nonlinear development with meditation practice. Indeed, the idea of a quadratic relation between brain activity and meditation proficiency can shed new light on the often contradictory findings on neural correlates of meditation ( Cooper et al 2022 ; see also Brefczynski-Lewis et al. 2007 ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The review by Cooper et al (2022) found that the results on mPFC activity was the most divergent of all network hubs investigated, which could be an indication that this area is especially prone to a nonlinear development with meditation practice. Indeed, the idea of a quadratic relation between brain activity and meditation proficiency can shed new light on the often contradictory findings on neural correlates of meditation ( Cooper et al 2022 ; see also Brefczynski-Lewis et al. 2007 ).…”
Section: Discussionmentioning
confidence: 98%
“…Decreased PCC activity is one of the most robust findings in studies on meditation, both as state and trait ( Fox et al. 2016 , Cooper et al 2022 ). PCC activity has been hypothesized to relate to being ‘caught up’ in experience, as in feeling attachment to or identifying with various things, such as holding on to an opinion, identifying as being a certain kind of person, or experiencing craving ( Brewer et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps the mind has to depart from the "ordinary" way of functioning via a sensed self/self-duality and identification with the observing self, before being able to "return" to a state that is in some ways transformed (with regards to boundarylessness) but in some ways similar (with regards to perspectival ownership). Interestingly, there is some support for nonlinear changes in brain activation with meditation experience (Cooper et al, 2022), and we report elsewhere that certain brain dynamics of our participants varied quadratically in relation to boundarylessness (Lindström et al, 2023). Briefly, the most relevant findings are that boundarylessness correlated negatively with brain activity in the posterior cingulate cortex/precuneus during mindwandering compared to a task targeting a minimal sense of self and we also found a quadratic relation in that those reporting low or high boundarylessness, as compared to those in the middle, showed more connectivity within the default mode network during rest, less brain activity in the medial prefrontal cortex during self-referential word processing, and less self-endorsement of words related to personal constancy.…”
Section: Discussionmentioning
confidence: 99%
“…The default mode network is particularly important as the processing of self-referential thought includes self-reflection (perspective-taking), future things, ruminating and remembering events in the past, which are all deictic RFT processes, with very relevant neurological pathways to self as content and the observer self. Interestingly, drug compounds that low the processing of the default mode network such as psilocybin lead to participants reporting the phenomenological experience of their sense of self such as ego (the self-stories, narrative self as content) dissolving, and this includes the boundary between their self and the environment ( Carhart-Harris et al, 2013 ; Lebedev et al, 2015 ; Pollan, 2015 ; Barrett and Griffiths, 2018 ), and mindfulness exercises have also been found to dissolve self to some degree ( Cooper et al, 2022 ), such as the body scan have led to similar effects such as dissolving bodily boundaries of self ( Hanley et al, 2020 ) and rigid patterns of defensive-self ( Garland et al, 2017 ). For full details of how interoception, embodied cognition of self, relates to entropy and predictive coding and some of these ideas that emerged decades ago, when the physicist Schrödinger (1942) in his seminal book, asked “ What Is Life?” (see Supplementary material 13 ).…”
Section: Embodied Cognition Entropy Markov Blanket Ca and Selfmentioning
confidence: 99%